Answer:
Explanation:
We have been given an expression, 11x+7=6x-3.
Step: Add or move the like terms.
Step: Solve the parts separately.
Step: Divide the expression by 5.
Therefore, the required value of x is -2.
11x+7=6x-3
move 6x to the other side
sign changes from +6x to -6x
11x-6x+7= 6x-6x-3 ( combine like terms)
11x-6x+7= -3
5x+7= -3
move +7 to the other side
sign changes from +7 to -7
5x+7-7= -3-7
5x=-3-7
5x=-10
divide both sides by 5 to get x by itself
5x/5= -10/5
answer:
x= -2
5.7m questions
7.4m answers